2006
DOI: 10.1108/03090590610712278
|View full text |Cite
|
Sign up to set email alerts
|

Considering unlearning in HRD practices: an Australian study

Abstract: Purpose -The purpose of this paper is to explore the level of consideration given to unlearning during human resource development interventions and to identify the methods being used to reinforce training and development. Design/methodology/approach -A self-administered questionnaire was given to a convenience sample of employers in regional Queensland and the Northern Territory, Australia. Analysis of responses using descriptive statistics was conducted to identify whether approaches differed in relation to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…For strategic change to be successfully executed in a turbulent environment, firms must unlearn or discard old routines to make way for new ones (Hutzschenreuter, Kleindienst, & Greger, ; Tsang, ). Becker, Hyland, and Acutt () reported that organizations with a defined HRD function are aware of the importance of unlearning as an integral part of embedding new learning. In prior research, the concept of “unlearning” has attracted many researchers from diverse fields, although most studies of unlearning have been case studies without statistical support and quantitative examination (Akgun, Lynn, & Byrne, ; Akgun, Byrne, Lynn, & Keskin, ).…”
Section: Introductionmentioning
confidence: 99%
“…For strategic change to be successfully executed in a turbulent environment, firms must unlearn or discard old routines to make way for new ones (Hutzschenreuter, Kleindienst, & Greger, ; Tsang, ). Becker, Hyland, and Acutt () reported that organizations with a defined HRD function are aware of the importance of unlearning as an integral part of embedding new learning. In prior research, the concept of “unlearning” has attracted many researchers from diverse fields, although most studies of unlearning have been case studies without statistical support and quantitative examination (Akgun, Lynn, & Byrne, ; Akgun, Byrne, Lynn, & Keskin, ).…”
Section: Introductionmentioning
confidence: 99%
“…This unlearning context has been analyzed in relation to the information acquisition processes relative to the markets (Sinkula, 1994(Sinkula, , 2002, and from different levels of analysis-individual (Day & Nedungandi, 1994), groupal (Becker, Hyland, & Acutt, 2006), of innovation (Akgün, Lyn, & Byrne, 2006), competitive (Lei, Slocum, & Pitts, 1999;Sinkula, 2002), etc. Though there exist no work on this subject, it is expected that this process of unlearning-learning will be applicable also to the process of internationalisation of the business, given its similarity to the processes of innovation (Bilkey & Tesar, 1977;Knight & Cavusgil, 2004).…”
Section: Export Intention Exploration and Unlearning Contextmentioning
confidence: 99%
“…Organizational memory develops with size and age of the organization; older organizations find unlearning more difficult as their practices have got embedded in the system, allowing very little scope for change (Argyris and Schon, 1978). Organiza-tions with low employee turnover might find unlearning difficult due to lack of new ideas entering the organization (Becker, Hyland and Acutt, 2006). This paper focuses on the appropriateness of AI as a developmental intervention to facilitate unlearning of explicit and implicit knowledge at individual, group, and organizational levels in organizations.…”
Section: Levels Of Unlearningmentioning
confidence: 99%
“…Other approaches that focus on problems or issues do not lay emphasis on past/current success and hence aggravate resistance to unlearn. According to Becker, Hyland and Acutt (2006), individual unlearning is the starting point for group or organizational unlearning, and individuals who believe they are experts in a specific field show more resistance to unlearn as they have invested a lot of time and resource creating their current knowledge, which is mostly internalized in the form of tacit knowledge (Zell, 2003).…”
Section: Appreciative Inquiry (Ai)mentioning
confidence: 99%
See 1 more Smart Citation